Βιοποικιλότητα άγριων μελισσών στις περιοχές Ακρωτήρι και Τσεκέρ Τσιφλίκ κατά τους χειμερινούς μήνες - Βασιλείου, Νικολέττα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Nowadays, our planet is under constant threat. This situation is likely to be due to a combination of biotic and abiotic factors, with the human being taking a leading and decisive role. Among the countless ecological and environmental issues that arise, one of the most critical matters is the decrease of the abundance and richness of pollinator species. Though unknown to many, most the Hymenoptera species belong to the category of wild bees. A key category, being considered responsible for one of the most important ecosystem services, the pollination of flowering plants, on which the whole system of world food production is based. The effort to protect and conserve these species is necessary, but to do so, we need to be familiar with the existing species of the island. In Cyprus, dealing with wild bees cannot be described as a very popular occupation, with the result that the only data available are the G.A. Mavromoustaki’s (1898-1968) publications. This diploma thesis aims at observing and recording the biodiversity of wild bees in areas of Limassol during the winter months, December to February.
Keywords: Wild; Solitary; Bees; Biodiversity; Akrotiri; Tserkez Tsiflik; Άγριες; Μοναχικές; Μέλισσες; Βιοποικιλότητα; Ακρωτήρι; Τζερκέζ Τσιφλίκ